Interseismic deformation above the Sunda megathrust recorded in coral microatolls of the Mentawai islands, West Sumatra - Natawidjaja, Danny H. (2012)
The geomorphology and internal stratigraphy of modern coral microatolls show that all the outer arc Mentawai islands of West Sumatra have been subsiding over the past several decades. These same islands rose as much as 3 m during the giant megathrust earthquakes of 1797 and 1833, and the current subsidence probably reflects strain accumulation that will lead to future large earthquakes. Average subsidence rates over the past half century vary from 2 to 14 mm yr−1 and increase southwestward, toward the subduction trench. The pattern is consistent with rates of subsidence measured by a sparse network of continuously recording Global Positioning System (cGPS) stations and with locking of a 400-km-long section of the underlying subduction megathrust, between about 1°S and 4°S. This record of subsidence and tilting, extending nearly a century into the past, implies that the region is advancing toward the occurrence of another giant earthquake. However, evidence of episodic rather than steady subsidence reflects a behavior that is more complex than simple elastic strain accumulation and relief. Most prominent of these episodes is an extensive emergence/subsidence couplet in about 1962, which may be the result of rapid, aseismic slip on the megathrust, between the islands and the trench. Lower subsidence rates recorded by the corals since about 1985 may reflect failure on many small patches within the locked section of the megathrust.